5(r+9)-2(1-9)=1

Simple and best practice solution for 5(r+9)-2(1-9)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(r+9)-2(1-9)=1 equation:


Simplifying
5(r + 9) + -2(1 + -9) = 1

Reorder the terms:
5(9 + r) + -2(1 + -9) = 1
(9 * 5 + r * 5) + -2(1 + -9) = 1
(45 + 5r) + -2(1 + -9) = 1

Combine like terms: 1 + -9 = -8
45 + 5r + -2(-8) = 1

Multiply -2 * -8
45 + 5r + 16 = 1

Reorder the terms:
45 + 16 + 5r = 1

Combine like terms: 45 + 16 = 61
61 + 5r = 1

Solving
61 + 5r = 1

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-61' to each side of the equation.
61 + -61 + 5r = 1 + -61

Combine like terms: 61 + -61 = 0
0 + 5r = 1 + -61
5r = 1 + -61

Combine like terms: 1 + -61 = -60
5r = -60

Divide each side by '5'.
r = -12

Simplifying
r = -12

See similar equations:

| 1/3y-5=3 | | (x^3+x^2+x+1)(11x-9)=0 | | -2+-13= | | -4(4y-6)-y=-2(y-4) | | f(-3)=(1/3)^x | | 26x+18=5(5x+7) | | 6-3x-11x+4= | | 9x-5x=6x+7x | | 9x+9=2x+9 | | (5x+8)-(7+4x)=8 | | 7-7(3c-2)+4(c-7)+3c=0 | | 25-2x=17+2x | | 11x+7y=2 | | 8n=-160 | | (5x+8)-(7+4y)=8 | | 5=x-17 | | 24=6(5-2a) | | -29=-25+r | | 0=1600-60x | | -9=m-(-5) | | -9/12-(-7/4) | | 7y-3x= | | 15x+(-4x)= | | 1/7*1/6 | | 2xy/5y | | -480=20x | | 4-p=5p+16 | | 522=29x | | 4x+5-2x=-19 | | 3[4x-(2x-7)]= | | a/1/a2= | | 1=v-(-12) |

Equations solver categories